Product and Service Innovation Strategies to Expand MSME Markets - Yani, Ahmad; Suparwata, Dewa Oka; Hamka (PT. LITERASI SAINS NUSANTARA, 2023)
Micro, Small, and Medium Enterprises are one of the important pillars in a country's economy. Despite their strategic role, MSMEs often face a number of challenges, such as intensifying competition, changing consumer tastes, evolving technology, and access to a wider market. This study aims to analyse product and service innovation strategies to expand the MSME market. This research employs a qualitative research approach, more precisely, a literature review, where data will be examined and explained by drawing upon information and textual materials collected from a variety of sources. The study results show that innovation in products and services plays a key role in the growth and sustainability of micro, small and medium enterprises. MSMEs play a vital role in the economy by creating jobs and contributing to sustainable economic growth. Innovation differentiates MSMEs from their competitors in an increasingly globalised and dynamic business environment. Innovative products and services can attract customer attention, provide a competitive advantage, improve product quality, and build long-term relationships with customers.